Modular synthesis of the pyrimidine core of the manzacidins by divergent Tsuji-Trost coupling - Bretzke, Sebastian; Scheeff, Stephan; Vollmeyer, Felicitas; Eberhagen, Friederike; Rominger, Frank; Menche, Dirk (Beilstein journal of organic chemistry, 2016)
Beilstein Journal of Organic Chemistry